INFLATION VALUE FORECASTING POST COVID-19 IN DENPASAR USING ARIMA - Mariati, Ni Putu Ayu Mirah; Setiawati, Luh Pande Eka; Dewi, Ni Luh Putu Sandrya (Graduate Program of Universitas Tarumanagara, 2023)
Forecasting is used to predict something that will happen in the future so that appropriate actions can be taken. ARIMA is a time series forecasting method that was developed where the observation data in a time series data interact. Inflation instability in Denpasar City in the future will make it difficult for the central bank and the government to determine policy. The Covid-19 pandemic has an impact on the value of inflation in Denpasar City. The purpose of this study is to estimate inflation in Denpasar City after Covid using the best ARIMA model. Inflation data was taken from BPS Denpasar City from January 2020 to August 2022. ARIMA analysis was carried out according to the Box-Jenkins procedure, namely searching the data, estimating parameters and significance tests, and determining the best ARIMA model. The results of the analysis show that the best ARIMA model is ARIMA (0,1,1). The results of this study indicate that monthly inflation in Denpasar City is likely to continue to increase. Based on these results, it is hoped that appropriate policies will be made to reduce inflation.